ANALISIS KEBUTUHAN PENGEMBANGAN BUKU AJAR PENDIDIKAN KEWARGANEGARAAN BERBASIS ARTIFICIAL INTELLIGENCE UNTUK PENGUATAN SMART AND GOOD CITIZEN - Dedek Helida Pitra; Sundari Utami; Lavandra Balti; Dara Nurfaizah (Jurnal Muara Pendidikan, 2025)
The development of artificial intelligence has driven the need for innovative learning materials capable of addressing the demands of digital literacy, media ethics, and twenty-first-century citizenship competencies. This study aims to analyze the needs for developing an Artificial Intelligence–based Civic Education textbook as an effort to strengthen the concept of the Smart and Good Citizen in higher education. The research employed a Sequential Explanatory Mixed-Methods approach involving 107 students and 4 lecturers through questionnaires, interviews, and curriculum document analysis. Data were analyzed qualitatively and quantitatively to map essential content, digital features, and relevant citizenship competencies. The findings show that 87% of respondents require an AI-integrated textbook to enhance students’ understanding of digital ethics and responsible AI use, thereby fostering citizens with integrity in the technological era. The study also reveals the need for adaptive learning features, digital democracy case studies, and the integration of AI-use ethics. The results further highlight a significant gap between conventional Civic Education materials and the demands of technology-based learning. The study concludes that the development of an AI-based Civic Education textbook is highly necessary to support contextual, interactive, and technologically relevant learning, and to effectively shape students into Smart and Good Citizens.